Spectrum of Benign Breast Diseases in Surgically Excised Specimens: A Clinicopathological Study - Nazma Kiran, Nausheen Henna, Ayesha Gohier, Nadia Aslam, Muhammad Faisal Javaid, Naveed Akhter, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Approximately 30% of female population suffers from benign breast diseases in anytime of their life. A comprehensive review of histopathological findings can tell us the behavior and type of the breast lesion and will also benefit the patient and the clinician to take the timely decision. Aim: To understand the histopathological pattern of benign breast diseases encountered in RMC teaching hospital, Sargodha. Methods: This descriptive study was undertaken in the Pathology Department, Rai Medical College, Sargodha, from January 2017 to December 2021. 146 breast lump specimens were included in the study. This study comprised of all those cases which were diagnosed as benign breast diseases regardless of age of the patient and excluded the cases that were malignant. Results: 146 cases of benign breast lesions were collected in the pathology department for a period of 5 years. The most frequently encountered lesion were fibroadenoma (45.8%), breast abscess (22.6%) and fibrocystic change (11.6%). The other benign lesions observed were granulomatous mastitis (7.5), gynaecomastia (5.4), sclerosing adenosis (2.7%), phyllodes tumor (2.0%), fat necrosis (1.3%) and tubular adenoma (0.6%). Conclusion: Benign lesions of the breast are more common as compared to malignant with a peak incidence in the 2nd and 3rd decade. Clinical evaluation followed by histopathological assessment provided the accurate diagnosis. Early excision, assessment and confirmation of the lesion on histopathology help us to distinguish benign from the malignant disease.